Changes in Food Intake Pattern of Nurses Working in Rapidly Rotating Shift - Subhashis Sahu and Manimala Dey (Al Ameen Medical College, 2011)
The aim of this study was to asses the affect of rapidly rotating shift work on food intake pattern on nurses. Forty nurses working in rapidly rotating shift and thirty five general duty nurses were randomly chosen from different government hospitals in the Paschim Medinipur district, West Bengal. It was observed that different gastrointestinal problems like loss of appetite, indigestion and acidity occurs more frequently among rotating shift nurses than the general duty nurses. In night shift worker, the number of full meals per 24 hour, appetite and eating satisfaction were significantly lower (p<0.0005) and the number of snacks were significantly higher (p<0.0005) than other shifts and general duty nurses. Intake of carbohydrate, protein and fat intake were significantly lower (p<0.0005) when nurses work in night shift and the fat intake were significantly lower in morning shift than other shifts and general duty nurses. The mean energy intake in night shift nurses was significantly lower (p<0.0005) than the other shifts and general duty nurses. It was also found that the calorie intake in nurses per 24 hours working in night shift was less than the ICMR recommended value. Probably desynchronization in food intake pattern led to different digestive problems in nurses working in night shift.